The Effect of the 1964 Revenue Act on the Sensitivity of the Federal Income Tax - Tanzi, Vito; Hart, Thomas P. (The Review of Economics and Statistics, 1972)
From 1954 up to 1964, when Congress approved a new Revenue Act, legal structure of individual income tax of United States remained virtually unchanged. That structure was substantially changed by Revenue Act of 1964. Under previous legislation rate structure had begun at 20 per cent and had ended at 91 per cent; new rate structure started at 14 per cent and ended at 70 per cent. The first bracket, to which 20 per cent rate had applied and which had included tax income of 0 to 2000 dollars, was replaced by four smaller brackets of 500 dollars each (or 1000 dollars for married persons) to which rates of 14, 15, 16 and 17 per cent, respectively, became applicable (Pechman, 1965). The most important but by no means sole objective of new Act was reduction of fiscal drag of Federal budget. Personal income tax liabilities were reduced by 6.7 billion dollars at 1964 levels of income. Further reductions in 1965 cut individual income tax revenues by an estimated total of about 11 billion dollars (Pechman, 1965, p. 247; Council of Economic Advisers, 1965, p. 65). This reduction in revenues was necessitated by characteristics of individual income tax revenue of growing at a somewhat faster rate than income. This high elasticity, together with relative importance of this tax, has made it a powerful automatic stabilizer in United States. However, as it came to be recognized in early part of 1960's, under certain circumstances, automatic stabilization can become an ambiguous blessing. In words of Council of Economic Advisers (CEA), the protection [that] it gives against cumulative downward movements of output and employment is welcome. But its symmetrical 'protection' against upward movements becomes an obstacle on path to full employment . (Council of Economic Advisers, 1963, p. 68). The 1963 CEA's Report continued by stating that: